Human papillomavirus antibody response following HAART initiation among MSM. (20th February 2017) - Combes, Jean-Damien; Clifford, Gary M.; Egger, Matthias; Cavassini, Matthias; Hirsch, Hans H.; Hauser, Christoph; Calmy, Alexandra; Schmid, Patrick; Bernasconi, Enos; Günthard, Huldrych F.; Franceschi, Silvia; Waterboer, Tim; et al.
Abstract : Objective: To describe effects of HAART on high-risk human papillomavirus (HPV) antibody response in HIV-positive MSM and the meaning of this response for subsequent HPV-related cancer risk. Design: Prospective seroepidemiological study of 281 HIV-positive MSM initiating HAART between 1995 and 2004 in the Swiss HIV Cohort Study. Methods: For each individual, two serum samples, one at HAART initiation (pre-HAART) and another 24 months later (post-HAART), were tested for L1 antibodies to HPV6, 11, 16, 18, 31, 33, 35, 45, 52 and 58, as well as HPV16-E6 antibodies, using a multiplex serology assay. Identification of HPV-related cancer included data linkage with Swiss cancer registries. Results: Pre-HAART, 45.2% were seropositive for any high-risk HPV-L1 and 32.4% for HPV16-L1. Sexual intercourse during the last 6 months was the only evaluated factor associated with L1 seropositivity pre-HAART. Seropositivity increased post-HAART to 60.5% for any high-risk HPV-L1 [prevalence ratio versus pre-HAART = 1.34, 95% confidence interval (CI) 1.14–1.57] and 48.0% for HPV16-L1 (prevalence ratio versus pre-HAART = 1.48, 95% CI 1.20–1.83), and seroconversion was significantly associated with both lower CD4 + cell count and CD4 + /CD8 + ratio ( P < 0.01). Only one individual was HPV16-E6-seropositive pre-HAART, but two more seroconverted post-HAART. Anal cancer incidence among the three HPV16-E6-positives post-HAART was significantly increased compared with HPV16-E6-negatives (incidence rate ratio = 63.1, 95% CI 1.1–1211). Conclusion: HAART-related immune reconstitution increases HPV-specific antibody responses, which may discriminate future anal cancer risk in this high-risk population.